The Relation Between Money, Income and Prices in South Africa - Kevin S. Nell (University of Kent, Department of Economics, 1999)
The main purpose of this paper is to determine whether inflation in South Africa has been caused by excessive monetary expansion over the period 1966-1997, or whether the money supply has merely been passive in the inflationary process. The analysis first draws on Friedman and Schwartz's (1982) theoretical exposition to transform South Africa's stable M3 money demand function into a theory of money, income and prices. Long-run price equations are then estimated with consumer price inflation as the relevant inflation variable, given that the M3 money demand function is deflated by consumer price inflation. To validate the econometric interpretation of the long-run price equations, causality tests based on the methodology developed by Pesaran et al. (1996) together with non-nested tests are used. These show that money and 'excess' money are endogenous to consumer price inflation and broad measures of inflation. The most important policy implication of an endogenously determined money supply is that a long-run analysis of inflation in South Africa should search beyond the realms of the Central Bank alone, and focus on the potential inflationary impact of structural and/or cost-push forces of inflation.
Keywords: C22; E31; E41; 330; exogenous/endogenous money supply; 'excess money'; causality tests; non-nested tests; Inflation; Geldmenge; Südafrika